Changing characteristics of the empathic communication network after empathy-enhancement program for medical students. Issue 1 (December 2018) - Yun, Je-Yeon; Kim, Kyoung; Joo, Geum; Kim, Bung; Roh, Myoung-Sun; Shin, Min-Sup
Abstract The Empathy-Enhancement Program for Medical Students (EEPMS) comprises five consecutive weekly sessions and aims to improve medical students' empathic ability, an essential component of humanistic medical professionalism. Using a graph theory approach for the Ising network (based onl 1 -regularized logistic regression) comprising emotional regulation, empathic understanding of others' emotion, and emotional expressivity, this study aimed to identify the central components or hubs of empathic communication and the changed profile of integration among these hubs after the EEPMS. Forty medical students participated in the EEPMS and completed the Depression Anxiety Stress Scale-21, the Empathy Quotient-Short Form, the Jefferson Scale of Empathy, and the Emotional Expressiveness Scale at baseline and after the EEPMS. The Ising model-based network of empathic communication was retrieved separately at two time points. Agitation, self-efficacy for predicting others' feelings, emotional concealment, active emotional expression, and emotional leakage ranked in the top 20% in terms of nodal strength and betweenness and closeness centralities, and they became hubs. After the EEPMS, the 'intentional emotional expressivity' component became less locally segregated (P = 0.014) and more directly integrated into those five hubs. This study shows how to quantitatively describe the qualitative item-level effects of the EEPMS. The key role of agitation in the network highlights the importance of stress management in preserving the capacity for empathic communication. The training effect of EEPMS, shown by the reduced local segregation and enhanced integration of 'intentional emotional expressivity' with hubs, suggests that the EEPMS could enable medical students to develop competency in emotional expression, which is an essential component of empathic communication.